ABOUT SOME FEATURES OF THE LANGUAGE OF IVAN POSOSHKOV’S WORKS - KHIZANTSYAN, ANNA (Bulletin of Yerevan University H: Russian Philology, 2019)
The article analyzes the issues of the publicist I.T. Pososhkov (the first third of the XVIII century), which represent as a unique mirror of Russia during the investigated period. We observe the time of writing, questions raised by the author and the proposed solutions of them. We also examined the grammatical features of Pososhkov’s issues. The results showed that the Russian literary language of the first third of the XVIII century was at the stage of formation.
Keywords: Russian literary language, I. T. Pososhkov, grammatical features, archaism, new language elements